2022
DOI: 10.1590/acb370403
|View full text |Cite
|
Sign up to set email alerts
|

The effects of valproic acid on skin healing: experimental study in rats

Abstract: To recognize the effects of valproic acid (VPA), an epigenetic drug, on the skin healing process. Methods: Sixty male Wistar rats were divided into two groups: the experiment treated with VPA (100 mg/kg/day); and the control, with 0.9% sodium chloride by gavage. Skin healing was studied in three moments (the third, the seventh, and the 14th day), evaluating the parameters: inflammatory reaction and its intensity (anti-LCA), angiogenesis (anti-CD34), collagen I and III (anti-collagen I, anti-collagen III and Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In another experiment using intraperitoneal administration, the results were similar 44 . However, in a study of our line of research on cutaneous healing, we noticed that the administration of VPA promoted a decrease in angiogenesis and collagen deposition, especially type-I collagen 47 .…”
Section: Discussionmentioning
confidence: 85%
“…In another experiment using intraperitoneal administration, the results were similar 44 . However, in a study of our line of research on cutaneous healing, we noticed that the administration of VPA promoted a decrease in angiogenesis and collagen deposition, especially type-I collagen 47 .…”
Section: Discussionmentioning
confidence: 85%
“…Few studies have reported the influence effect of VPA on skin healing, with controversial results. On the other hand, SV-VPA causes cutaneous drug eruptions [8]. Cutaneous drug eruptions associated with SV-VPA can range from hyperpigmentation [9] to severe Stevens-Johnson syndrome [10].…”
Section: Discussionmentioning
confidence: 99%